Effects of pendulum tuned mass dampers on the dynamic response of jacket platforms. (1st April 2022) - Pourzangbar, Ali; Vaezi, Mostafa
Abstract: We investigate effects of pendulum tuned mass damper (PTMD) configuration as well as structural excitation frequency by ocean waves on the dynamic response of a jacket platform. To do this, an offshore jacket platform equipped with a PTMD with different values of frequency ratio ( β ), damping ratio ( ξ d ) and mass ratio ( m ‾ ) is numerically simulated in ANSYS software under the action of irregular waves with different values of structural excitation frequency ratio (α). The results of the numerical simulations are validated against the experimental and numerical data available in the literature. The validations were in complete agreement with the benchmarking data. The results suggest that with a constant β, an increase in ξ d of about 20 times reduces the standard deviation of the deck displacements ( σ ) tblf about 7.41%. Further, with an increase in β, σ increases when β > 1 and decreases when β ≤ 1 . Regarding the pendulum mass ratio, an increase in m ‾ of about 14 times results in a 12.91% reduction in σ within the range of ξ d ≤ 0.15 . Out of the latter range (i.e. for ξ d > 0.15 ), σ is not significantly affected by m ‾ . Considering σ as the fitness function, the most optimal configuration for the PTMD system is achieved for α = 1.2, β = 1 and ξ d = 0.2 . Highlights: Effects of a PTMD configuration on dynamic response of a jacket platform is studied employing ANSYS. The numerical simulations validated using various experimental benchmarking data. Interaction between waves' excitation and PTMD configuration are investigated on the response of the platform. An optimized configuration for the PTMD system is proposed based on the waves' loading in the jacket platform.